2000
DOI: 10.1002/j.2048-7940.2000.tb01901.x
|View full text |Cite
|
Sign up to set email alerts
|

Journal Writing As a Complementary Therapy for Reactive Depression: A Rehabilitation Teaching Program

Abstract: Brief, recurrent, reactive, or situational depression is a common and costly comorbidity that affects chronically ill patients and their family members. This article describes a program that teaches those individuals how to monitor and cope with symptoms of depression by writing daily in a journal. Twenty patients and family members attended teaching sessions at which videotaped scenes of other patients managing symptoms of depression were shown. After viewing the six scenes, participants wrote about their rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 56 publications
(57 reference statements)
1
22
0
Order By: Relevance
“…These interventions, or evidence-based activities, information and guidelines, have been shown to improve the quality of life of caregivers as well as the successful management of HPN home care. 12, 15–19 The HPN Family Caregivers Website provides scientifically-based algorithms with step-by-step instructions for practicing the most common self-care procedures and resolving HPN home care problems. While the website content about managing HPN is specific to this patient population, the information guiding caregivers to care for their own health can be generalized to other caregivers who provide similar complex home care for other illnesses.…”
Section: Hpn Family Caregivers Websitementioning
confidence: 99%
See 4 more Smart Citations
“…These interventions, or evidence-based activities, information and guidelines, have been shown to improve the quality of life of caregivers as well as the successful management of HPN home care. 12, 15–19 The HPN Family Caregivers Website provides scientifically-based algorithms with step-by-step instructions for practicing the most common self-care procedures and resolving HPN home care problems. While the website content about managing HPN is specific to this patient population, the information guiding caregivers to care for their own health can be generalized to other caregivers who provide similar complex home care for other illnesses.…”
Section: Hpn Family Caregivers Websitementioning
confidence: 99%
“…19, 25 Persons with reactive depression sleep poorly, ignore their health, obtain less social support and are at a higher risk for comobordities. 26 However, previous research has found that caregivers with increased depression are responsive to telehealth or online nursing interventions.…”
Section: Hpn Family Caregivers Websitementioning
confidence: 99%
See 3 more Smart Citations